Implementation of Sharia Crowdfunding in the Principle of Sharia Compliance in Hasanah Waqf Products at PT Bank Syariah Indonesia Tanjungkarang - Mustofa, Ulul Azmi; Ilmalana, Selma; Kurniawan, Agus; Suherman, Suherman (Journal of Contemporary Applied Islamic Philanthropy, 2024)
Purpose: Crowdfunding in Islamic Banks has the function of mediating the collection of funds on the social side. This research aims to see how the implementation of Sharia crowdfunding at Bank Syariah Indonesia KC Tanjung Karang and also see its suitability with the principles of Sharia compliance. Methodology: This research uses a descriptive qualitative approach. The author took data from interviews with the Operating Manager, Customer Service, and Funding Officer of PT Bank Syariah Indonesia KC Tanjung Karang, to see the implementation of the concept of sharia crowdfunding in the collection and distribution of funds from the Hasanah Waqf product. Findings: The results of the analysis show that Bank Syariah Indonesia KC Tanjung Karang implements the concept of sharia crowdfunding in its product, Wakaf Hasanah. Bank Syariah Indonesia KC Tanjung Karang also implements the concept of sharia crowdfunding by the principles of sharia compliance.